PENYULUHAN PEMBUATAN NUGGET IKAN LELE SEBAGAI SOLUSI CAMILAN SEHAT UNTUK ANAK DI DESA KUALU KECAMATAN TAMBANG KABUPATEN KAMPAR PROVINSI RIAU - Mulyani, Isma; yolandika, clara; Metalisa, Rindi; Darfia, Novreta Ersyi; Lesmana, Indra; Heltonika, Benny (Politeknik Negeri Lampung, 2022)
The number of processed fish circulating in the market does not necessarily guarantee that thepreparation has a level of cleanliness and nutritional content that is good for health. One form ofprocessed food favored by children is nuggets. By being processed into nuggets, fish becomes easyto eat, making it suitable to be used as food for children. The purpose of this activity is (1) to introducevarious processed fish that are healthy, nutritious, delicious and definitely liked by children, (2) todisseminate information about various kinds of processed fish that are liked by children, and (3) toteach ways to process fish-based foods. This activity was carried out in Kualu Village, KamparRegency, Riau Province. Activities are carried out through counseling with several stages, namelylectures, direct demonstrations and practice, giving leaflets, and monitoring. The achievement ofactivities in the form of counseling about the making of catfish nugget and its handling by housewivesin area 5, RW 01, Kualu Village, Tambang District, Kampar Regency. The women who were taughtwere women from RT 10. The conclusion of this activity was that by increasing the ability of women inRT 10 RW 01 Kualu Village, Tambang District, Kampar Regency in making catfish nuggets, theoutreach program was successful in making catfish nuggets increase the insight of mothers in makingvariations of fish-based foods.